Open inventor and PREMO - Wang, Dejuan; Reynolds, Graham J.; Herman, Ivan (1996)
Abstract: "PREMO is an emerging international standard for the presentations of multimedia objects including computer graphics. Open Inventor [superscript TM] is a commercially available 'de facto' standard for interactive computer graphics packaged as a library of objects. In this report we consider whether the concepts and objects of PREMO are sufficient to represent a professional quality system, such as Open Inventor. By comparing PREMO with Open Inventor, we hope to show that PREMO's computer graphics environment model can properly describe the procedure by which Open Inventor realizes graphics applications, and PREMO's event model can naturally model Open Inventor's event handling mechanism in a natural way. The scene graph is a core concept in Open Inventor. Most Open Inventor functions rely on various operations over scene graphs. The construction, edition and traversal of scene graphs are shown to be readily implemented based on the current set of PREMO objects. Graphics rendering, event handling and the scene graph constitute the fundamental parts of Open Inventor, other Open Inventor functionalities can be constructed from these. We conclude that since these three fundamental parts of Open Inventor can be properly modelled and implemented by PREMO, the concepts and objects of PREMO are sufficient to represent Open Inventor."
Keywords: Computer graphics; Multimedia systems; Object-oriented programming (Computer science)